Analisa Faktor yang Mempengaruhi Kejadian Ikterik pada Neonatus - Tri Dian Lian Sari; Lilla Maria; Rahmawati Maulidia (Universitas Baiturrahim, 2023)
Jaundice is a symptom that is common in newborns. This jaundice usually disappears by the end of the first week or no later than the first ten days. This study aims to analyze the factors that influence the incidence of jaundice in neonates. This study used the literature review method by searching journals using three databases: PubMed, Google Scholar, and SpringerLink. Journal inclusion criteria published 2016 - 2021. Research results of jaundice in neonates. Factors that influence the incidence of neonatal jaundice in the Asian region, especially Southeast Asia, are maternal and perinatal. Maternal factors include gestational age, complications, pregnancy (incompatibility, ABO blood group, Rh and DM), type of delivery, and race. Perinatal factors include neonatal asphyxia, infection, birth trauma, low intake of breast milk, low birth weight (LBW), gender, and medication. The management of neonatal jaundice includes exposing the baby to the sun, phototherapy, adequate nutritional intake, and adequate breastfeeding. For this reason, health education and support from the husband and family are needed for the mother so that the baby does not experience jaundice.